Development and validation of educational manual for the promotion of breastfeeding - Costa, Priscila Bomfim (2013)
The aim of this study was at developing and validating an educational manual promoting breastfeeding. It was a methodological study in which 17 illustrations and their respective captions were developed based on existing literature.  A validation of appearance and content was conducted by five health professionals and validation of appearance by 17 women in their postpartum period who were being attended to in a maternity ward in Fortaleza-CE, Brazil, from March to May 2009. Regarding the degree of relevance of the figures and captions, the Content Validity Index was calculated, with an excellent rate of 0.97 after modifications and exclusions as suggested during the evaluation. The final version of the manual consisted of 13 figures and captions. The use of this manual both during the pre-natal and postpartum phases is believed to facilitate nursing in that it represents an illustrated medium that can provide answers for the mothers’ questions, promoting breastfeeding. DOI:https://doi.org/10.15253/2175-6783.20130006000012